2006
DOI: 10.1002/yea.1434
|View full text |Cite
|
Sign up to set email alerts
|

The ORF YNL274c (GOR1) codes for glyoxylate reductase in Saccharomyces cerevisiae

Abstract: The enzyme glyoxylate reductase reversibly reduces glyoxylate to glycolate, or alternatively hydroxypyruvate to D-glycerate, using either NADPH or NADH as a co-factor. The enzyme has multiple metabolic roles in different organisms. In this paper we show that GOR1 (ORF YNL274c) encodes a glyoxylate reductase and not a hydroxyisocaproate dehydrogenase in Saccharomyces cerevisiae, even though it also has minor activity on α-ketoisocaproate. In addition, we show that deletion of the glyoxylate reductase-encoding g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
1
11
0
1
Order By: Relevance
“…Our Basic Local Alignment Search Tool (BLAST) search against the protein database of yeast Saccharomyces cerevisiae revealed that YNL274C (a NADPH-dependent glyoxylate reductase) is most similar to dCtBP, although it lacks the PXDLS-and RRT-binding motifs (Rintala et al 2007). So far, worms appear to be the simplest animal that contains CtBP.…”
Section: Resultsmentioning
confidence: 98%
“…Our Basic Local Alignment Search Tool (BLAST) search against the protein database of yeast Saccharomyces cerevisiae revealed that YNL274C (a NADPH-dependent glyoxylate reductase) is most similar to dCtBP, although it lacks the PXDLS-and RRT-binding motifs (Rintala et al 2007). So far, worms appear to be the simplest animal that contains CtBP.…”
Section: Resultsmentioning
confidence: 98%
“…The activity of the endogenous S. cerevisiae glyoxylate reductase GOR1 [13] and the A. thaliana GLYR1 [14] he GLYR1 gene was codon optimised for expression in yeast. Both genes were overexpressed in S. cerevisiae from the same multicopy plasmid and the activity with glyoxylic acid and NADPH was measured from crude extracts.…”
Section: Resultsmentioning
confidence: 99%
“…In S. cerevisiae , two glyoxylate reductase isoforms have been purified [23,24] but only one gene, GOR1 , encoding glyoxylate reductase activity has been identified [13]. Deletion of the glyoxylate reductase, GOR1 , led to increased biomass formation after diauxic shift, which was thought to be caused by increased NADPH availability [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations